(3GdOhQ GdYdGLi dJUeje GdMOGFb GdYdGLjI HGdeSJTajGJ (B: s (3OQGSI MGdI GdMOjbI GdYdGLjI HeSJTajGJ GdGWaGd (B/ s - (3CMeO GdWGgQ eMeO CMeOs; (3MSGe eMe`O YHOGdYRjR (B: s; (3hdjO YHOGdefYe YHO GdbGOQ (B: s ((3GdbGgQI (B: s (3CMeO GdWGgQ eMeO CMeO (B: s, 2017)
(3JYO GdMOGFb GdYdGLjI ai GdeHGfj GdUMjI VQhQI ef GdVQhQjGJ GdhXjajI YfO GdJUeje(B: (3aGdMOGFb GdYdGLjI dOjgG GdYOjO ef GdahGFO hcPdc GdJCKjQ GdfaSi Ydi GdeQjV ai cd eDSSGJ GdQYGjI GdUMjI(B: (3hbO RGO GdhYi ai GdBhfI GdCNjQI Edi GdMGLI dNdb HjFGJ JMGcj GdHjFI GdWHjYjI dci JSGYO Ydi Jbdjd GdJhJQ(B: (3adPdc hLH GdGgJeGe HhLhO Jdc GdMOGFb HGdeSJTajGJ cCeQ ege deG jSge Hg ai SQYI TaGA GdeQjV(B. (3ceG QcR GdHMK Ydi GdeSJTajGJ hNGUg eSJTajGJ GdCWaGd hPdc fXQG dCf GdYdGL HGdeSJTajGJ dg JCKjQ cHjQ Ydi SdhcjGJ GdCWaGd(B: (3hef gfG XgQJ GdeTcdI GdQFjSjI GdJj jJfGhdgG GdHMK HGdOQGSI hgi bdI GdGSJaGOI ef GdMOGFb GdYdGLjI hNUGFUgG ai JbfjGJ GdYdGL s
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdgfOSI (B- (3bSe GdgfOSI GdeYeGQjIs
(3UOQ GjVG cbQU eOeLs
Keywords: (3GdMOGFb GdYdGLjI s; (3eSJTajGJ GdCWaGd s; (3fXQjGJ GdYdGLs